2006
DOI: 10.1080/09585190600965449
|View full text |Cite
|
Sign up to set email alerts
|

The effects of HRM practices and antecedents on organizational commitment among university employees

Abstract: The effects of HRM practices and antecedents on organizational commitment among university employees Smeenk, S.G.A.; Eisinga, R.N.; Teelken, J.C.; Doorewaard, J.A.C.M. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim. Abstract This paper examines which factors affect organizational commitment among Dutch university employees in two faculties with different academic identities (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
3
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 74 publications
6
97
3
8
Order By: Relevance
“…8 2017 most relevant to their current jobs were able to attain more positive commitment outcomes and had less of intention to quit (Burke, 1995). Some findings from empirical work on employees in the West are supportive of a link between training provision and OC (Bartlett, 2001;Owens, 2006;Wayne, Shore, & Liden, 1997) but some other studies found insignificant relation (Shore & Barksdate, 1998) or significant but negative relation (Smeenk, Eisinga, Teelken, & Doorewaard, 2006). The reasons of such mixed results may partly be because of market imperfection in which a company is not always successful to employ a person whose skill is compatible to what the company needs.…”
Section: Training Provisionmentioning
confidence: 84%
“…8 2017 most relevant to their current jobs were able to attain more positive commitment outcomes and had less of intention to quit (Burke, 1995). Some findings from empirical work on employees in the West are supportive of a link between training provision and OC (Bartlett, 2001;Owens, 2006;Wayne, Shore, & Liden, 1997) but some other studies found insignificant relation (Shore & Barksdate, 1998) or significant but negative relation (Smeenk, Eisinga, Teelken, & Doorewaard, 2006). The reasons of such mixed results may partly be because of market imperfection in which a company is not always successful to employ a person whose skill is compatible to what the company needs.…”
Section: Training Provisionmentioning
confidence: 84%
“…This judgment is challenged by others who argue that managerialism works against its own intentions of efficient and effective quality improvement (see Bryson 2004;Davies and Thomas 2002;Thornhill et al 1996;Trow 1994b). The latter situation is what we call a 'managerialism contradiction' (Smeenk et al 2006) and the purpose of this paper is to examine its possible existence by testing two lines of reasoning. In the first one, managerialism is suggested to have a direct effect on the quality of performances ('direct effect argumentation').…”
Section: Introductionmentioning
confidence: 92%
“…Finally, although university employees are the prototype of knowledge workers and organizational commitment is a particularly interesting research area for university employees (Smeenk et al 2006), additional research in other areas of knowledge work such as for example professional service companies is necessary to extend the generalizability of our findings. In these organizations, indirect managerial control such as instilling pride is assumed to be particularly important because it is more difficult to control employees' outcomes and quality of work (Alvesson and Willmott 2002).…”
Section: Limitations and Future Researchmentioning
confidence: 99%